2010
DOI: 10.1002/htj.20301
|View full text |Cite
|
Sign up to set email alerts
|

Critical heat flux enhancement in pool boiling using alumina nanofluids

Abstract: The pool boiling characteristics of dilute dispersions of alumina nanoparticles in water were studied. Consistent with other nanofluid studies, it was found that a significant enhancement in critical heat flux (CHF) can be achieved at modest nanoparticle concentrations (<0.1% by volume). During experimentation and subsequent inspection, formation of a porous layer of nanoparticles on the heater surface occurred during nucleate boiling. This layer significantly changes surface texture of the heater wire surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…11. The variation in the heat flux values were similar to the trend observed by Bang et al [4], Hegde et al [15] and Kim [18]. Wherein heat flux increased with concentration, a reverse trend was observed in the studies of Kim and Bang [17].…”
Section: Discussion On Changed Boiling Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…11. The variation in the heat flux values were similar to the trend observed by Bang et al [4], Hegde et al [15] and Kim [18]. Wherein heat flux increased with concentration, a reverse trend was observed in the studies of Kim and Bang [17].…”
Section: Discussion On Changed Boiling Performancesupporting
confidence: 90%
“…Therefore, the reasons for this conflicting performance may be related to differences in the surface characteristics between the boiling surface and nano-fluids. Hegde et al [15] found that the roughness of the heater surface considerably decreased changes in the boiling characteristics. In order to confirm the nanoparticle coating over the heater surface, SEM images of the bare surface of the heater were taken before starting the experiment and the surface roughness (Ra value) was measured using the Mitutoyo Surf test.…”
Section: Discussion On Changed Boiling Performancementioning
confidence: 98%
“…Many other studies consider the primary reason for CHF enhancement is due to the surface coating effect [99,100,106,[108][109][110][111]. For example, Bang and Chang [99] conducted an experimental study on boiling heat transfer characteristics of nanofluids with nanoparticles suspended in water using different concentrations of alumina nanoparticles.…”
Section: Nucleate Pool Boiling Heat Transfer and Chf Mechanisms Of Namentioning
confidence: 97%
“…Therefore, the reasons for this conflicting performance may be related to differences in the surface characteristics between the boiling surface and nanofluids. Hegde et al [22] found that the surface roughness of the heater surface decreased, which changed the boiling characteristics. Modification of the heater surface due to change in surface roughness (Ra value) was measured using the Mitutoyo Surftest-SJ301, a surface profilometer.…”
Section: Effect Of Pressure On Boiling Heat Transfermentioning
confidence: 98%